5G Wales Unlocked - Dylan Henderson (Welsh Economic Review (WER), 2024)
This paper examines Department for Culture, Media and Sport (DCMS) and Welsh Government support for 5G deployment in rural areas of Wales. This project introduced several use cases based on 5G-enabled digital applications in Monmouthshire and Blaenau Gwent. The findings highlight the ongoing challenges associated with 5G deployment in rural Wales, and the current lack of a business model for 5G deployment by Mobile Network Operators (MNOs) in such areas. The report illustrates how the public sector may collaborate with private actors to develop an experimental approach to 5G deployment challenges faced in rural areas. This approach is based on an iterative learning process, in which small-scale experimental actions aimed at identifying sources of demand and understanding the potential impacts of new technology solutions are established. The report suggests that policy action is required at multiple levels of governance in such experimentation to address the challenge of deploying new 5G, and to ensure that firms and public service provision in rural parts of Wales are not disadvantaged.
Keywords: 330